MODEL FINANCIAL DISTRESS YANG MEMPENGARUHI MINAT MAHASISWA MUSLIM MILENIAL PADA PINJAMAN ONLINE SYARIAH - Ramadhan, Rizki; Arfiani, Mutia; Ahyar, Rizki (LPPM Universitas Bina Bangsa, 2025)
This research aims to examine whether there is an influence of parental income, financial literacy, and place of residence on the interest of millennial Muslim students in Sharia online loans. The population in this study is Muslim millennial students of the Accounting Study Program at Aceh Polytechnic, class of 2021/2022. The sample size in this study is 50 respondents. The sampling technique uses purposive sampling method. The research method used is quantitative with data sources in the form of primary data. Data collection in the research was conducted using Google Forms. The data analysis method employed was multiple linear regression analysis using SPSS version 25. The results of this study indicate that residence has a partial influence on the interest of millennial Muslim students in Sharia online loans. Meanwhile, parental income and financial literacy do not affect the interest of millennial Muslim students in Sharia online loans. Simultaneously, the variables of parental income, financial literacy, and residence have a significant impact on the interest of millennial Muslim students in Sharia online loans